A Systematic Review of Tests Assessing Stroke Knowledge. Issue 3 (May 2017) - Hou, Wen-Hsuan; Hoffmann, Tammy; Huang, Yi-Jing; Wu, Tzu-Yi; Chen, Sheng-Shiung; Hsieh, Ching-Lin
Abstract : Background: Accurate assessment of stroke knowledge (SK) is fundamental to the successful understanding of, monitoring of, and intervening to improve the SK of patients and the public. Purpose: The purpose of this study is to perform a systematic review of the existing SK tests and appraise their conceptual basis, feasibility, and psychometric properties. We conducted 2-step searching of MEDLINE, CINAHL, PsycINFO, and Scopus electronic databases from January 1, 2000, to December 31, 2014, to identify relevant SK tests for the appraisal. Results: Our study found 59 SK tests, out of a total of 93 articles, with full content available that had been referred to in the published literature. Ten of them had been used in more than 1 study, and 2 (the Stroke Knowledge Test and the Stroke Action Test) of them have had at least 1 of their psychometric properties validated. Only 1 test (the Stroke Knowledge Test) was developed using rigorous methodology, covers a wide range of concepts, and met all feasibility criteria; however, its limitations include no articulated conceptual basis, inadequate internal consistency reliability ( α = .65), and lack of some validated psychometric properties. Conclusions: Our study revealed that current available tools are not sufficiently able to accurately and reliably assess SK to promote stroke prevention and management. Clinical Implications: This study highlights the attention of applying current SK tests and need for revising existing tests or developing a new test.